Increasing productivity of tile craftsman in Darmasaba Village, Badung District - I Made Dhita Prianthara; Putu Vierda Lya Suandari; Vitalia Fina Carla Rettobjaan (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The lack of knowledge of tile craftsmen regarding ergonomic working attitudes, lack of knowledge regarding business management starting from bookkeeping and marketing strategies, as well as knowledge regarding innovation in clay-based products has caused the tile crafts industry in Darmasaba Village to experience many problems ranging from health problems and economic problems. This community service implementation is carried out to overcome partner problems through training in work attitudes, business management and product innovation to increase the productivity of roof tile craftsmen. This method of implementing community service is generally carried out through several stages, namelypreliminary survey, coordination with related parties, socialization of activities, and implementation of activities and evaluation of activities. The results of community service showed that roof tile craftsmen had an understanding of appropriate work attitudes for ergonomics, business management and product innovation based on the results of the pre-test and post-test questionnaire assessments. Roof tile craftsmen were also enthusiastic about participating in community service events from start to finish. Of all the participants who attended the implementation of community service, they showed an increase in knowledge of the material presented.